2019
DOI: 10.1016/j.aca.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extraction method and storage of dry tissue on marine lipids and fatty acids

Abstract: Please note that this is an author-produced PDF of an article accepted for publication following peer review. The definitive publisher-authenticated version is available on the publisher Web site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
(61 reference statements)
1
13
0
1
Order By: Relevance
“…Their PLs contain a large proportion of polyunsaturated fatty acids (PUFAs) in the chemical structure and are particularly susceptible to rancidity and oxidation to affect the product quality (Legako, Dinh, Miller, & Brooks, ). But they are also the main lipolysis substrates for the generation of healthful free fatty acids, such as eicosapentaenoic acid (EPA, 20:5n‐3) and docosahexaenoic acid (DHA, 22:6n‐3) (Sardenne et al, ; Simopoulos, ). Therefore, it is worth to quantitatively analysis the PLs profile of these two fish and to investigate their change during the processing.…”
Section: Introductionmentioning
confidence: 99%
“…Their PLs contain a large proportion of polyunsaturated fatty acids (PUFAs) in the chemical structure and are particularly susceptible to rancidity and oxidation to affect the product quality (Legako, Dinh, Miller, & Brooks, ). But they are also the main lipolysis substrates for the generation of healthful free fatty acids, such as eicosapentaenoic acid (EPA, 20:5n‐3) and docosahexaenoic acid (DHA, 22:6n‐3) (Sardenne et al, ; Simopoulos, ). Therefore, it is worth to quantitatively analysis the PLs profile of these two fish and to investigate their change during the processing.…”
Section: Introductionmentioning
confidence: 99%
“…Drying has been only used as a method for collecting lipids economically in the marine (fish) and biofuel (algae) industries. 11,12 We applied this method to remove lipids effectively, and as a result, amounts of lipids exuded from the tissue during the drying step. In detailed evaluation for lipid removal efficiency, the dried tissue showed rapid and complete lipid elimination, while the wet tissue revealed remaining lipids after a 60 min delipidation period.…”
Section: Discussionmentioning
confidence: 99%
“…61 According Folch et al, 56 the only advantage of using the Bligh and Dyer method 50 is the reduction in the solvent/sample ratio; 1 part tissue to 3 parts in the chloroform/methanol method instead of 1 part tissue to 20 parts chloroform/methanol. This procedure has been widely used 62,63 ; Bell et al, 64 extractedlipids from Atlantics almon (Salmo salar) using the procedure described by Folch, 56 like wise Gigliotti et al, 65 reported on lipid extraction from the Atlantic Krill (Euphausia superba), Ramanathan and Das, 66 also extracted lipids from Scomberomorus commerson using the method described to study the oxidation of lipids from ground fish in the presence of antioxidants. This method has also been used for the extraction of lipids from Atlantic mackerel (Scombers combrus), 67 in the shark species Eusphyra blochii and Carcharhinus bleekeri.…”
Section: Folch Methodsmentioning
confidence: 99%